Determination of Irrigation Water Quality of Lake Beysehir and Other Water Sources Used in Irrigation of Çumra Plain - ZENGIN, M.; KARAKAPLAN, S.; ERSOY, ILKNUR (Asian Journal of Chemistry, 2010)
In this research, irrigation water quality and pollutions of Lakes Beysehir and Sugla, Dams Apa and May used in irrigation of Çumra Plain were determined. Canal Çarsamba which is leading from Lake Beysehir to Çumra Plain and has about 150 km length is connected with Lake Sugla, Dams Apa and May along the route. In the irrigation water samples collected at four different times and from five points pH, EC, Ca2+, Mg2+, Na+, K+, CO32–, HCO3–, Cl–, SO42–, NO3–, Fe2+, Cu2+, Mn2+, Zn2+ and B were also analyzed and from these results SAR, RSC and quality classes were also determined. It was evaluated that all of the water samples had moderate alkaline pH values, class II salty and class I alkalinity (C2S1), class I RSC, class I and II B level and from Lake Beysehir to Dam May along the Canal Çarsamba, nitrate and heavy metals increased and boron contents decreased.